Let us assume temporarily that when we die we cease to exist. A nonexistent thing cannot be affected by anything. For example, it is impossible to kill a nonexistant chicken, move a nonexistant piece of matter, or eat a nonexistant pizza. We did not exist before we were borne. We were borne (we came into existence). We ceased to exist when we died. Since nothing can effect a nonexistant thing, the only variable for something nonexistent is its existence (which we shall designate as "e"). Now Here are the above three steps in terms of e: e=0 e=1 e=0 The object came into existence. Before this the only variable the object had was e, which was equal to zero. Therefore that variable has to be the cause of the change (since it is the ONLY variable). So: IF e=0 THEN e=1 Since time is not a variable that matters to this equation, the transition from e=0 to e=1 takes no time. "IF e=0 THEN e=1" really means "e cannot equal 0". This time rule does not hold true for e=1, however, because existing things ARE influenced by exterior things. Our equation only looks at the e variable, but when e=1 there are an infinite number of other variables that come into play. When e=0, however, e is the only variable. So, applying our rule (IF e=0 THEN e=1) we get: e=0 e=1 e=0 *Since e=0, THEN e=1 e=1 Therefore if we cease to exist after we die, we come into existence again. Wheather or not the non-e variables are the same each time is not something we can find from this equation. So the fact that we exist now is proof that we will always exist.